Histopathological pattern of thyroid lesions in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background and Objective:Thyroid gland lesions occur globally with geographical variation in incidence and histopathological pattern related to age, sex, dietary and environmental factors. There is, however, no published histological study from northwestern Nigeria; hence, we undertook this study to describe the spectrum, frequency, age and sex distribution of thyroid gland lesions seen in Kano, as well as compare the findings with previous studies done in Nigeria and elsewhere.Materials and Methods:This is a retrospective descriptive study of all thyroidectomy specimens received from January 1st, 2002 to December 31st, 2011 at the histopathology department of Aminu Kano Teaching Hospital, Kano, Nigeria.Results:Five hundred and twenty-two thyroid gland lesions were diagnosed during the ten year period with a female to male ratio of 6.4:1. The ages range from 5 months to 86 years with a mean age at presentation of 36.3 years and relative peak age of incidence occurring in the 30-39 years group. The most common entity was goitre (57.2%) with a mean age at presentation of 37.5 years. It was followed by thyroid adenomas (15.7%) and thyroid carcinomas (12.6%). Specifically among cancers, papillary carcinoma predominated (53%), followed by follicular carcinoma (33.3%) and medullary carcinoma (9.1%). There were 36 cases (6.9%) of thyroglossal duct cysts and 28 cases (5.4%) of toxic hyperplasia while thyroiditis was uncommon with only 2 cases (0.4%).Conclusion:This study shows that thyroid gland diseases are common in Kano and are seen in both genders with a striking female preponderance. It revealed a higher incidence of papillary carcinoma over follicular carcinoma, a reverse of the finding of an earlier clinicopathological study on thyroid gland diseases in Kano. The age and sex incidences as well as the histological featuresof thyroid lesions in this study are, however, similar to reports from other local and international studies.